Veredas: an important Cerrado phytophysiognomy for bryophytes (Research, Society and Development, 2021)
The present study aimed to know the bryophytes occurring in Veredas of the southern region of Goiás and Minas Gerais, Brazil. The collection was performed from February to December 2014, in four areas of Veredas: two in Quirinópolis, one in Gouvelândia (Goiás) and one in Monte Alegre de Minas (Minas Gerais). Twenty one families, 27 genera and 36 species (15 hepatic, 20 mosses and 1 hornworts) were found. Four species are new records for the state of Goiás, and two new records for the state of Minas Gerais.